Studies On Invitro Analysis Of Sargassum Wightii Against Human Simplex Virus (HSV) (Medico Legal Update, 2020)
Introduction: Human simplex viruses are ulcerative diseased found in skin and genital organs dependingupon the strain. It affects an individual at least once in a lifetime by direct contact with an infected person.There are two strains of HSV predominantly found are HSV-1 and HSV-2. HSV-1 infects the pharynx andoral region, whereas HSV-2 infects the genital areas of sexual contact.Materials and Method: The crude extract of S. wightii on the proliferation of Vero cells was assessed bythe neutral dye uptake method. Various fold of serially diluted solvent crude extracts showed cytotoxicconcentration50 (CC50) at 750 and 500mg/mL of ethyl acetate and methanol extract, respectively.Results: The Antiviral activity of solvent crude extract against HSV-1 showed significant reduction of viruson Vero cells. Among the solvent crude tested, the ethyl acetate showed effective IC50 against HSV-1 at 300mg/mL.Conclusion: The seaweed S. wightii is a natural source in treating the pathogen HSV-1 and it clearlyindicated that, the marine brown algae S. wightii possess strong antiviral activity with slight cytotoxic effect.